The great surge : the ascent of the developing world - Radelet, Steven C., 1957- (Simon&Schuster, 2015)
"The Great Surge tells the remarkable story of this unprecedented economic, social, and political transformation. It shows how the end of the Cold War, the development of new technologies, globalization, courageous local leadership, and in some cases, good fortune, have combined to dramatically improve the fate of hundreds of millions of people in poor countries around the world. Most importantly, The Great Surge reveals how we can fight the changing tides of climate change, resource demand, economic and political mismanagement, and demographic pressures to accelerate the political, economic, and social development that has been helping the poorest of the poor around the world,"--Amazon.com.